2017
DOI: 10.5604/12321966.1235166
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis for operating active wheelchairs in non-urban settings

Abstract: Introduction. A wheelchair is a special vehicle designed specifically for people with walking limitations. One of the types is an active wheelchair. This is a manually propelled wheelchair, the design and structure of which maximise the mobility of its given user at the expense of accepted instability. Objective. The aim of this study was to identify and present a hierarchy of potential incidents causing a health hazard and reducing the mobility of individuals with ambulatory disability who use active wheelcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The quantitative study from this report demonstrated that the respondents' spontaneous answers concerning the area of integration confirmed that this area did not belong to the crucial needs which should be satisfied [15]. Similar results were obtained by other researchers [14,37].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The quantitative study from this report demonstrated that the respondents' spontaneous answers concerning the area of integration confirmed that this area did not belong to the crucial needs which should be satisfied [15]. Similar results were obtained by other researchers [14,37].…”
Section: Discussionsupporting
confidence: 83%
“…A study by M. Sochańska-Kawiecka showed that as many as 45% of respondents considered that a disabled person and the family cannot count on support of organizations and institutions functioning in Poland, which indicates that the system does not function in an optimum way [15]. A similar number of respondents mentioned the lack of reliable information concerning the assistance available on the part of the support institutions [11,37]. The respondents often deny that the family is covered with care when a disabled person occurs in it.…”
Section: Discussionmentioning
confidence: 99%
“…Sea water causes significant problems in using durable structural materials; it may also lead to injury (in the case of people moving in wheelchairs, the water drying on the wheelchair seat and the formed salt residue may cause skin laceration). In turn, wind and swaying may result in less stability for people moving around the yacht; thus, it is vital to eliminate the risk of being hit by designing, e.g., foot shields for people moving on wheelchairs (due to spinal cord damage, foot numbness, and no sensation of pain, accidental bumps may be very dangerous for users [ 69 ]), and the impact of air temperature at high humidity may lead to hypothermia, etc. Considering the environment’s specific character is essential in product design [ 70 ].…”
Section: A Proposal For An Algorithm For the Design Of Innovative At ...mentioning
confidence: 99%
“…Independent mobility increases vocational and educational opportunities, reduces dependence on caregivers and family members and promotes feelings of self-reliance [8]. Every wheelchair consists of two engineering subsystems assembled into one structural and functional entity, such as the transport system which includes wheels, the drive, steering and braking mechanisms, and the orthotic system for body positioning which includes the body support systemback and side supports, seat, foot rest and other devices stabilising selected parts of the body [9]. There remains a vast need for quality wheelchairs around the world.…”
Section: Introductionmentioning
confidence: 99%